Effect of an InGaP spacer layer on the luminescence properties of InP/InGaP quantum structures - Byun, Hye Ryoung; Ryu, Mee-Yi; Song, Jin Dong; Lee, Chang-Lyoul (KOREAN PHYSICAL SOC, 2015)
The optical characteristics of InP/InGaP quantum structures (QSs; quantum dots + quantum dashes) grown by using a migration enhanced epitaxy method have been investigated using temperature-dependent photoluminescence (PL) and time-resolved PL (TRPL). An InGaP spacer layer with different thicknesses (15, 30, and 50 nm) was grown on the InP QSs in order to identify the effect of the InGaP spacer layer on the luminescence and the carrier dynamics of InP QSs. As the thickness of the InGaP layer was increased from 15 to 50 nm, the PL peak exhibited a blueshift, and the PL intensity increased, which are attributed to the increased carrier confinement in the vertical direction due to the increased height and reduced width and length of QSs. The PL decay time demonstrated a strong dependence on the emission wavelength and the temperature. In addition, the decay time for InP QS samples with InGaP layers of 30 and 50 nm exhibited different emission-wavelength dependence than that for the InP QS sample with an InGaP layer of 15 nm. These results demonstrate that the optical and the structural properties of InP QSs are significantly affected by varying the thickness of the InGaP spacer layer.
Keywords: TIME-RESOLVED PHOTOLUMINESCENCE; DOTS; SPECTRA; LASERS